An Issue of Scale: The Challenge of Time, Space and Multitude in Sustainability and Geography Education - Frode Skarstein; Lili-Ann Wolff (MDPI AG, 2020)
The field of geography is important for any sustainability education. The aim of geography education is to enable students to understand the environment, its influence on human activity, and how humans influence the environment. In this article we present a study on how the interplay between the three pillars of sustainability thinking (environment, society and economy) play out on smaller and larger scales of time, space and multitude in geography education. In this paper, we argue that central issues in high quality sustainability education in geography relates to students’ deeper grasp of how to shift between magnitudes of time, space and multitude patterns. We show how an appreciation of many core issues in sustainability education require students to understand and traverse different magnitudes of the scalable concepts of time, space and multitude. Furthermore, we argue and exemplify how common sustainability misconceptions arise due to an inability to make the cognitive shift between relevant magnitudes on these scalable concepts. Finally, we briefly discuss useful educational approaches to mediating this problem, including the use of digital tools in order to allow geography teachers to facilitate the students’ better understanding of different magnitudes of slow, fast, small and large scale entities and processes.